Effect of emotional exhaustion on satisfaction with studies and academic procrastination among Peruvian university students - Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Castillo-Blanco, Ronald; Caycho-Rodríguez, Tomás; Villafuerte de la Cruz, Avelino Sebastián; Dávila Villavicencio, Roussel (Frontiers in Education, 2023)
Objective: To examine the effect of emotional exhaustion on satisfaction with studies and academic procrastination among Peruvian university students.Method: An explanatory study was conducted with 1,011 Peruvian university students (60.2% women and 39.8% men). The Brief Satisfaction with Studies Scale (EBSE), Emotional Exhaustion Scale (ECE), and the Academic Procrastination Scale (EPA) were used to measure the variables.The results revealed that the explanatory model had an acceptable fit,  2 (1) = 7.7, p = .006, CFI = .982, RMSEA = .081, SRMR = .021. These findings provide evidence that emotional exhaustion negatively affects satisfaction with studies (β = −.30, p < .001) and positively influences academic procrastination (β = .15, p < .001).emotional exhaustion is decisive in satisfaction with studies and academic procrastination.